An addiction model‐based mobile health weight loss intervention in adolescents with obesity. Issue 2 (16th August 2018) - Vidmar, A. P.; Pretlow, R.; Borzutzky, C.; Wee, C. P.; Fox, D. S.; Fink, C.; Mittelman, S. D.
Summary: Background: Clinical approaches to treating childhood obesity can be expensive and poorly reimbursed, and often produce suboptimal results. It has been theorized that overeating may have addictive qualities, and a sizable number of adolescents with obesity endorse addictive habits. Interestingly, few weight management interventions have tested techniques founded in addiction medicine principles. We therefore performed a pilot study of an addiction model based mHealth weight loss intervention in adolescents. Methods: Adolescents with obesity were recruited from an multidisciplinary weight management clinic (EMPOWER). Adolescents without significant obesity comorbidities, who exhibited signs of addictive eating, based on the Yale Food Addiction Scale, were enrolled in a pilot study of an interactive, addiction‐based, weight loss smartphone app with coaching (http://clinicaltrials.gov : NCT02689154). The app was designed to help subjects omit problem foods, avoid snacking and reduce meal size. A contemporary cohort of adolescents who completed the EMPOWER program were evaluated. Feasibility of recruitment, adherence, retention rates, BMI change and cost of intervention were examined. Results: Eighteen participants were recruited to app intervention. App participants had higher retention (100% vs. 37%) and lower total cost per patient ($855.15 vs. $1428.00) than the EMPOWER clinic participants. App participants exhibited a significant decrease in zBMI and %BMIp95 over the 6 months ( p  < 0.001 and p  = 0.001), which was comparable to the age‐matched EMPOWER program completers ( p  = 0.31 and p  = 0.06). Conclusions: An addiction medicine‐based mHealth intervention targeted for adolescents was feasible to implement, resulted in high retention and adherence rates, and reduced zBMI and %BMIp95 in a more cost‐effective manner than an in‐clinic intervention.